Addition of EP2 agonists to an FP agonist additively and synergistically modulates adipogenesis and the physical properties of 3D 3T3-L1 sphenoids. (August 2021) - Ida, Yosuke; Watanabe, Megumi; Umetsu, Araya; Ohguro, Hiroshi; Hikage, Fumihito
Highlights: Addition of EP2 agonists to FP agonist modulate adipogenesis of the 2D and 3D cultured 3T3-L1 cells. EP2 agonists synergistically altered physical properties of the 3T3-L1 sphenoid with FP agonist. 3D culture was useful technique for evaluation of adipocytes by PG derivatives. Abstract: The additive effects of prostaglandin (PG)-EP2 agonists on a PG-FP agonist toward adipogenesis in two- or three-dimension (2D or 3D) cultures of 3T3-L1 cells was examined by lipid staining, the mRNA expression of adipogenesis related genes, and extracellular matrixes (ECMs) including collagen molecules (Col) -1, -4 and -6, and fibronectin (Fn), and the sizes and physical properties of 3D sphenoids, as measured by a micro-squeezer. The results indicate that adipogenesis induced 1) an enlargement in the sizes of 3D sphenoids, 2) a substantial enhancement in lipid staining, the expression of the PPar γ,   Ap2 and  Leptin genes, and 3) a significant decrease in the stiffness of the 3D sphenoids. These effects were inhibited by bimatoprost acid (BIM-A), but 4) adipogenesis induced significant down-regulation of Col1 and Fn, and the significant up-regulation of the Col4 and Col6 genes were unchanged by BIM-A. On the addition of an EP2 agonist, such as omidenepag (OMD) or butaprost (Buta), to BIM-A, 1) the sizes of the 3D sphenoids were further decreased, 2) lipid staining was decreased (2D; OMD, 3D; Buta) 3) the stiffness of the 3D sphenoids was increased by Buta, 4) the expression of PPar γ was up-regulated (2D; Buta) or unchanged (3D), the expression of Ap2  was down-regulated (2D; OMD) or up-regulated (3D; Buta), and the expression of  Leptin was increased (2D), 5) the expression of all four (OMD) or all except Col4 (buta) in 2D, and Col1 and Col4 (OMD) in 3D were up-regulated. These collective findings indicate that the addition of an EP2 agonist, OMD or Buta significantly modulated the BIM-A induced suppression of adipogenesis as well as physical properties of 2D and 3D cultured 3T3-L1 cells in different manners.